Synergy of Production Training And Market Targeting in Improving Quality and Competitiveness of MSMES in Underdeveloped Regions - Dwi Intan Cantika Putri Hendrayana; Eka Nova Yulianti; Mashudi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving national economic growth, particularly in underdeveloped regions with limited access to developmental resources. Beyond being the largest employment sector, MSMEs significantly contribute to local economic empowerment. However, MSME actors in these disadvantaged areas often face critical challenges, including low product quality and inadequate implementation of effective and adaptive marketing strategies. These issues limit the competitiveness of MSME products in both local and national markets. This study aims to comprehensively analyze the impact of the synergy between production training and market targeting training on improving product quality and the competitiveness of MSMEs in underdeveloped regions. Employing a qualitative methodology through library research, the study synthesizes secondary data from scholarly journals, research reports, and relevant publications. The findings indicate that integrating production training which encompasses quality enhancement, efficiency improvements, and product innovation with marketing training covering branding strategies, digital marketing, and consumer segmentation simultaneously can elevate product standards and expand market reach. These results underscore the necessity of designing holistic, contextual, and sustainable training programs to address the structural challenges faced by MSMEs in underdeveloped areas. An integrated training synergy proves more effective in cultivating competent, adaptive entrepreneurs with heightened competitiveness amidst increasingly complex market dynamics.